Meeting with Gabriela Mistral: From womanship to logos in Repertorio Americano - Mendiola Vásquez, Melissa (2021)
In our literary encounter, Mistral invites us to the fraternal American love of the womanish, positioning ourselves in the world with the appropriationof our logos and Latin American realities. She joins her voice of America’s teacher, transcending the symbolic, and transforms the logos of the feminine.